2013
DOI: 10.1093/jjco/hyt014
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic Body Radiation Therapy for Stage I Non-small-cell Lung Cancer: A Historical Overview of Clinical Studies

Abstract: Because of difficulties with stabilization, breathing motion and dosimetry, stereotactic body radiotherapy for lung cancer has only been practiced for the past 15 years. However, a large amount of case data has rapidly been accumulated in recent years. Stereotactic body radiotherapy for Stage I non-small-cell lung cancer has been actively investigated in inoperable patients since around 1995, and a number of clinical trials have been undertaken. Early studies from 2001 presented a 3-year local control rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
33
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 34 publications
2
33
0
Order By: Relevance
“…Considering the robustness of these findings within many studies worldwide, it is fair to state that SBRT has been proven to be comparable to outcome of lobectomy and lymph node dissection [69,70]. Indeed, in the International Association for the Study of Lung Cancer database, which also comprises a large, relatively non-selected group of patients, the 2-year overall survival was 68% (66-70%) [56].…”
Section: Stereotactic Radiotherapy or Stereotactic Ablative Radiotherapymentioning
confidence: 75%
See 3 more Smart Citations
“…Considering the robustness of these findings within many studies worldwide, it is fair to state that SBRT has been proven to be comparable to outcome of lobectomy and lymph node dissection [69,70]. Indeed, in the International Association for the Study of Lung Cancer database, which also comprises a large, relatively non-selected group of patients, the 2-year overall survival was 68% (66-70%) [56].…”
Section: Stereotactic Radiotherapy or Stereotactic Ablative Radiotherapymentioning
confidence: 75%
“…45 studies concerning SABR in early stage NSCLC have been reported [56]. 13 studies including 996 patients were prospective, and 32 studies including 2645 patients were retrospective.…”
Section: Stereotactic Radiotherapy or Stereotactic Ablative Radiotherapymentioning
confidence: 99%
See 2 more Smart Citations
“…Stereotactic body radiotherapy (SBRT) allows improved local control and overall survival for patients with inoperable early-stage non-small cell lung cancer (NSCLC) (1)(2)(3)(4). The two most important factors for SBRT of NSCLC are accurate positioning for tumor targeting and minimizing side effects (3,5).…”
Section: Introductionmentioning
confidence: 99%